2011
DOI: 10.1071/rd11015
|View full text |Cite
|
Sign up to set email alerts
|

Restricted feed intake in lactating primiparous sows. I. Effects on sow metabolic state and subsequent reproductive performance

Abstract: The effects of feed restriction (60% of anticipated feed intake; Restrict; n=60) during the last week of a 21-day lactation in primiparous sows compared with feeding at 90% of anticipated feed intake (Control; n=60) on sow metabolic state, litter growth and sow reproductive performance after weaning were compared. Metabolisable energy (ME) derived from feed was lower, ME derived from body tissues was higher and litter growth rate was reduced (all P<0.05) in Restrict sows during the last week of lactation. Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
45
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 34 publications
5
45
1
4
Order By: Relevance
“…In addition, the sows submitted to feed restriction presented greater backfat thickness loss (+1.9 mm). This result is consistent with the findings of other authors (Foxcroft et al, 1995;Eissen et al, 2003;Vinsky et al, 2006;Quesnel, 2009;Schenkel et al, 2010;Patterson et al, 2011). Although backfat thickness does not reflect total fat body reserves, changes in this parameter may indicate that the sow is in negative energy balance (Jittakhot et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the sows submitted to feed restriction presented greater backfat thickness loss (+1.9 mm). This result is consistent with the findings of other authors (Foxcroft et al, 1995;Eissen et al, 2003;Vinsky et al, 2006;Quesnel, 2009;Schenkel et al, 2010;Patterson et al, 2011). Although backfat thickness does not reflect total fat body reserves, changes in this parameter may indicate that the sow is in negative energy balance (Jittakhot et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Restricted-fed sows presented higher protein (+2.92 kg) and lipid (+6.95 kg) losses compared with control-group sows. Vinsky et al (2006) and Patterson et al (2011) observed similar losses in sows submitted to feed restriction during lactation. Several authors suggest that the nutritional and metabolic changes in lactating sows may have deleterious effects on dam biology, with negative impacts on follicle development, and consequently on embryo development and on the number of piglets born in the next litter (Foxcroft et al, 2007;Ashworth et al, 2009;Quesnel, 2009;Schenkel et al, 2010;Hoving et al, 2011).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations